PENGARUH AUDIT TENURE, FEE AUDIT, DAN UKURAN PERUSAHAAN TERHADAP KUALITAS AUDIT - Khaerunnissa Wahrudin (2022)
This study is a quantitative study that aims to examine the effect of the variables audit tenure, audit fee, and company size on audit quality. This study uses financial sector companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2020 period as samples. The sampling technique used purposive sampling method and obtained 60 companies with a total sample of 180. The audit quality in this study was measured using the earning surprise benchmark proxy. The analytical technique used is logistic regression analysis with SPSS program and a significance level of 5% (0.05). The results showed that (1) audit tenure had no effect on audit quality, (2) audit fee had no effect on audit quality, and (3) company size had a significant positive effect on audit quality.